Risk and risk management of spillover effects: Evidence from the literature - Christian Eckert (Risk Management and Insurance Review, 2020)
In this article, we provide a comprehensive review of the existing theoretical and empirical literature regarding spillover effects (effects of a crisis event in an announcing firm on other firms). In particular, we focus on the mechanism behind spillover effects and investigate factors that drive spillover effects. The results of our literature analysis show that spillover effects are most often significantly negative, that is, lead to losses in nonannouncing firms and depend on certain events and firm characteristics. On this basis, we derive implications for the risk management of spillover effects. Taking previous work on certain individual risk-management measures into account, we are the first to provide a holistic spillover risk-management process.
Keywords: 330